2014
DOI: 10.1002/2013wr014650
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet‐based multiscale performance analysis: An approach to assess and improve hydrological models

Abstract: The temporal dynamics of hydrological processes are spread across different time scales and, as such, the performance of hydrological models cannot be estimated reliably from global performance measures that assign a single number to the fit of a simulated time series to an observed reference series. Accordingly, it is important to analyze model performance at different time scales. Wavelets have been used extensively in the area of hydrological modeling for multiscale analysis, and have been shown to be very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 38 publications
0
38
0
1
Order By: Relevance
“…Yan and Gao (2007) mother wavelets which could be used for wavelet decomposition; however, it has been demonstrated that the choice of the mother wavelets does not affect the results to a great extent for rainfall (Rathinasamy et al, 2014). In case I(a) the noise-signal ratio is quite high in the range of 2.7-3 (Table 1), such that the effect of the noise is felt up to scale 7 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Yan and Gao (2007) mother wavelets which could be used for wavelet decomposition; however, it has been demonstrated that the choice of the mother wavelets does not affect the results to a great extent for rainfall (Rathinasamy et al, 2014). In case I(a) the noise-signal ratio is quite high in the range of 2.7-3 (Table 1), such that the effect of the noise is felt up to scale 7 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Following the approach of Rathinasamy et al (2014), Yan and Gao (2007), and Hu and Si (2016), we test MSES using a set of case studies including stationary and non-stationary synthetic data. The details of the case studies and the wavelet power spectra are given in Table 1 and Fig.…”
Section: Testing Mses With Synthetic Datamentioning
confidence: 99%
See 3 more Smart Citations